Efektivitas ekstrak daun akar kucing (Acalypha indica) dalam meningkatkan pertumbuhan ikan Nila, Oreochromis niloticus - Ratusmanga, Jihan; Hutagaol, Anggun F.; Manoppo, Henky; Lantu, Sartje; Tumbol, Reiny A.; Mokolensang, Jeffrie F.; Kaligis, Erly Y. (e-Journal BUDIDAYA PERAIRAN, 2022)
The purposes of research were to examine the effect of extract of Acalypha indica leaf on the growth of Nile tilapia and determine the dose of leaf extract that could enhance the growth of tilapia optimally. The fish used were Nile tilapia taken from the Tatelu Center for Freshwater Aquaculture with an average weight of 3.79Â±0.50 g. The medicinal plant A. indica was collected from around the Faculty of Fisheries and Marine Science complex and from the North Bolaang Mongondow area. After being washed, the leaves were dried and then ground to obtain leaf powder. Leaf flour was then extracted by maceration method with 95% alcohol solvent. After being concentrated, the extract was then used as a treatment with different concentrations, including A: 0 g extract/kg feed, B:10 g extract/kg feed, C:20 g extract/kg feed, D:30 g extract/kg feed and E: 40g extract/kg feed. The data collected consisted of absolute growth, daily growth and relative growth. The results showed that the extract of A. indica leaf added to the feed had a significantly effect on the growth of tilapia indicated by an increase in absolute growth, daily growth, and relative growth (p<0.05). The best fish growth was achieved in fish fed with feed with the addition of 20 g extract/kg feed. In conclusion, leaf extract of A. indica can increase the growth of Nile tilapia